Gamma radiation induced variations in corn marigold (Glebionis segetum) and their RAPD-based genetic relationship - KAPOOR, MANISH; KUMAR, PRABHAT; LAL, SHANT (The Indian Journal of Agricultural Sciences, 2014)
The present investigation was conducted during the kharif season of 2010-2012 to study hormesis, morphological and biochemical attributes associated with mutation and purification of novel types in corn marigold. The seeds of Glebionis segetum were treated with gamma rays (Source 60Co) at the dose of 20, 40, 60, 80 and 100 Gy were sown in the field along with control (un-irradiated seeds). Low doses of gamma irradiation resulted in hormesis and induced encouraging novelties, while the higher doses induced higher degree of abnormalities which led to mortality. The M2 seeds were sown to observe their characters and mutants in each population. Five promising mutants, viz. S1-S3 at 20 Gy and S4-S5 at 40 Gy gamma irradiation treatments were tagged, screened and checked for stability of characters for genetic study and possible uses of the traits. RAPD molecular marker technique was used for the study of genetic divergence and establishment of distinctiveness or similarity between the mutants developed as a result of mutagenic treatment.